Two cases of differentiation syndrome with ocular manifestations in patients with acute promyelocytic leukaemia treated with all-trans retinoic acid and arsenic trioxide - Newman, A.R. (Am J Ophthalmol Case Rep, 2018)
PURPOSE: To describe two cases of differentiation syndrome presenting with ocular manifestations including bilateral chorioretinopathy in patients with acute promyelocytic leukaemia treated with all-trans retinoic acid and arsenic trioxide differentiation therapy. OBSERVATIONS: This observational case series identifies two patients at a single tertiary institution diagnosed with differentiation syndrome with associated ophthalmic involvement. Both patients reported bilateral reduction in visual acuity at days fourteen and ten respectively following initiation of differentiation therapy in addition to developing other systemic manifestations of differentiation syndrome. Both patients received the same chemotherapeutic regimen including both all-trans retinoic acid and arsenic trioxide as well as ten days of routine differentiation syndrome prophylaxis with oral prednisolone. Case 1 presented with bilateral pale yellow sub-retinal lesions concentrated at the posterior poles with ocular coherence tomography (OCT) evidence of bilateral multifocal areas of focal RPE elevation and adhesion to the thickened outer retina with interspersed sub-retinal fluid. Fluorescein angiography revealed areas of early hyperflouresence corresponding to the yellow chorioretinal lesions with late diffuse leakage of fluid into the subretinal space. Case 2 presented with a similar characteristic retinal findings on fundoscopy and optical coherence tomography. Both patients experienced rapid improvement in the visual symptoms and marked resolution of the sub-retinal fluid within seven to fourteen days of onset with excellent long-term visual outcome. Both patients achieved molecular remission after induction and received standard consolidation and maintenance therapy without visual disturbance. CONCLUSION AND IMPORTANCE: Ocular manifestations of differentiation syndrome have been only recently recognised. We present a case series of two patients with differentiation syndrome with ocular involvement. Common to both presentations was the presence of bilateral reduction in visual acuity with multifocal serous retinal detachment secondary to chorioretinopathy. The visual outcome from both presentations was excellent with rapid normalisation of visual acuity and resolution of the sub-retinal fluid with only the first case having their differentiation therapy temporarily withheld during the acute phase of illness.